Using Behavioural Economics For Rather than Against Consumers – A Practitioner's Perspective - Monique Goyens (Intereconomics, 2018)
Behavioural economics can be a powerful tool in achieving consumer policy goals, by nudging people to make healthy, sustainable and cost-conscious choices. It can also, however, be used against consumers' interests by misleading and deceiving them by exploiting their biases.
Keywords: 330